Genetic similarities of Escherichia coli isolated from different substrates of the broiler production chain - Teles, Pedro Filipe de Souza (2021)
Brazil is the largest exporter of chicken meat and poultry farming is one of the most important productive segments, despite major losses due to the bacterium Escherichia coli, which is also a zoonotic microorganism. The objetive of this study was to isolate E. coli and to evaluate its transmissibility potential from the field to chicken meat using the Pulsed Field Gel Electrophoresis (PFGE) technique. Environmental samples (poultry litter, soil and water) were collected from broiler farms located in the South of Brazil where the majority of the Brazilian poultry production occurs. In addition, chicken meat (gizzard, heart, drumette and tulip) samples were collected from local supermarkets. As results, 47.36% of the samples were positives for E. coli. Furthermore, 10 pairs of clones of E. coli were found always in the same substrate (two waterwater pairs; three soil-soil pairs and five meat-meat pairs) using PFGE. These findings suggest that certain strains of E. coli may have habitat preferences, making the transfer from one substrate type to another more difficult to occur. Moreover, since no clones were found between environmental samples and chicken meat, it is possible to imply a low risk of E. coli transmissibility throughout the chicken meat production chain.